The Use of Contemporary Mobile Banking Service in Islamic Banks: Perspective of Young Customers - Ambia Masthura Yussaivi; Carol Y Lu; Moch Edman Syarief; Dwi Suhartanto (Jurnal Internasional Penelitian Bisnis Terapan, 2021)
This study examines the factors that influence the attitudes and perceptions of the young customers towards the use of mobile banking services and AI-enabled mobile banking services. The research questionnaire was distributed using Google Form to customers using Islamic banking mobile banking services in Indonesia with a total sample of 204 young Muslim customers. Partial least square was used to test technology-based differential effects (attitudes towards AI, relative advantage, trust, and security of mobile banking) and non-technology based (need for service, quality of service) as well as factors of religiosity on the use of mobile banking services and AI-enabled mobile banking service. This study results in the findings that the construct of trust, attitudes towards AI, religiosity, and relative advantage are the main determinants of mobile banking adoption intentions. It also shows the gap between young customers in trust levels, attitudes towards AI, religiosity, and perceived relative advantage between the two dependent variables. Finally, the trust construct has the greatest impact on the use of mobile banking and AI-enabled mobile banking services.